CARVING THE FUTURE OF EDUCATION: A DATA-DRIVEN AND SWOT STRATEGIC PLAN FOR QUALITY IMPROVEMENT - Shelty Deity Meity Sumual; Joulanda Altje Meiske Rawis; Jeffry Sony Junus Lengkong; Yuliana Hartono; Jeff Lapian (EDUCATIONE, 2025)
Sustainable education transformation requires evidence-based and contextually relevant planning strategies. This study explores the integration of data-based planning with SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis to improve the strategic planning process in educational institutions. Employing a descriptive qualitative approach through a literature review method, this research examines secondary data obtained from accredited national journals, reputable international journals, and academic books published between 2013 and 2023. The study highlights that the use of valid and measurable data—such as national assessments, satisfaction surveys, and institutional performance indicators—significantly enhances the accuracy of SWOT analysis. This integrative approach enables the formulation of more accurate, reflective, and results-oriented educational strategies. However, the implementation of this model still faces several challenges, including low levels of data literacy among educators, limited access to integrated information systems, and the lack of structured training in strategic planning at the school level. This study contributes to the body of knowledge in education management by offering a conceptual framework that combines data-driven decision-making with SWOT analysis. The implications underline the need to strengthen institutional capacity and promote policy support for data-based planning to ensure adaptive and sustainable improvements in education quality.